Ekonomi Religiusitas dalam Industri Kecantikan: Analisis Kritis Integrasi Nilai-Nilai Islam dan Praktik Bisnis di Dr. Ferihana Beauty Clinic - Pradana, Aqsha Dinda; Gusti Rian Saputra (Jurnal Ekonomi STIEP, 2025)
This study examines the integration of Islamic values in the ethics practices of Indonesia's rapidly growing beauty industry, which saw a 5% growth in Q1 2023 with 9% projected by 2026. Using qualitative descriptive methods with case study and phenomenological approaches, the research analyzes Dr. Ferihana Beauty Clinic's operations through interviews, observations, and document studies. The findings demonstrate that implementing Islamic principles of honesty and professionalism enhances service quality, customer satisfaction, and sustainable business performance, while fostering ethical corporate culture. However, the study's limited sample representation from one clinic in Yogyakarta and exclusion of external factors suggest need for broader research. The results recommend that halal-certified beauty businesses should maintain religious values as competitive advantages while adapting to market dynamics.